The Implementation of Good Corporate Governance Perspective: A Case Study on BUMDes Samsam - Desak Made Mya Yudia Sari (AIBPM Publisher, 2024)
The role of Village-Owned Enterprises (BUMDes) aims to realize village independence in managing their finances in increasing the economy and village income. BUMDes Samsam is one of the community organizations that perform well because it is able to provide remaining business results in accordance with the ratified household budget rules. One thing that must be fulfilled is accountability for village financial management implementation activities. Accountability is often associated with Good Corporate Governance, including the financial activities of BUMDes. This research investigated the characteristics of accountability implemented by BUMDes Samsam's management. The research method used with case studies was proposed by Yin. The research was conducted at BUMDes Samsam on four informants who had direct contact with financial management accountability practices. Qualitative data was collected by observation, interviews, and documentation. The research results show that the accountability of implementation applies the characteristics of participation, transparency, kinship, honesty, loyalty, and integrity. This research can provide theoretical and practical implications that can influence village economic performance through BUMDes becoming independent villages